Endothelium Activation during Severe Yellow Fever Triggers an Intense Cytokine-Mediated Inflammatory Response in the Liver Parenchyma - Fábio Alves Olímpio; Luiz Fábio Magno Falcão; Marcos Luiz Gaia Carvalho; Jeferson da Costa Lopes; Caio Cesar Henriques Mendes; Arnaldo Jorge Martins Filho; Carlos Augusto Moreira da Silva; Vanessa do Socorro Cabral Miranda; Lais Carneiro dos Santos; Fellipe Souza da Silva Vilacoert; Ana Cecília Ribeiro Cruz; Vanessa Costa Alves Galúcio; et al. (Pathogens, 2022)
Yellow fever (YF) is a pansystemic disease caused by the yellow fever virus (YFV), the prototype species of the family Flaviviridae and genus Flavivirus, and has a highly complex host-pathogen relationship, in which endothelial dysfunction reflects viral disease tropism. In this study, the in situ endothelial response was evaluated. Liver tissue samples were collected from 21 YFV-positive patients who died due to the disease and five flavivirus-negative controls who died of other causes and whose hepatic parenchyma architecture was preserved. Immunohistochemical analysis of tissues in the hepatic parenchyma of YF cases showed significantly higher expression of E-selectin, P-selectin, intercellular adhesion molecule-1, vascular cell adhesion molecule-1, and very late antigen-4 in YFV-positive cases than in flavivirus-negative controls. These results indicate that endothelium activation aggravates the inflammatory response by inducing the expression of adhesion molecules that contribute to the rolling, recruitment, migration, and construction of the inflammatory process in the hepatic parenchyma in fatal YF cases.